If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(n+4)=-1+5n
We move all terms to the left:
-2(n+4)-(-1+5n)=0
We add all the numbers together, and all the variables
-2(n+4)-(5n-1)=0
We multiply parentheses
-2n-(5n-1)-8=0
We get rid of parentheses
-2n-5n+1-8=0
We add all the numbers together, and all the variables
-7n-7=0
We move all terms containing n to the left, all other terms to the right
-7n=7
n=7/-7
n=-1
| F(x)=-4(1/4)x | | 11w–10w–-1=18 | | (x+14)=(4x-25) | | 8-d-3d=-4 | | F(x)=4x^2-3x-5 | | (3x-1)^2-25x^2=0 | | 39-r=7-3(5r-6) | | 5+3x=9x-6 | | 49/14=35/x | | 3x+4*2x+60=35 | | 5x+2=−2x−19 | | -16+10=14n-16 | | 1326=16t^2 | | 688-r=128 | | 7/8x-5/3x=3 | | 9a+3a-6=32 | | 49d^2-36d+0=0 | | 1x(56)=31 | | (1/2)x-3=(1/5)x+6 | | 8/10=x/12 | | 7x+2-(3x+5)=17 | | -4-8=6y+32 | | 7x+-1=3x+1 | | -16+8x=7(x-3) | | 6v+8-v=5(v+3) | | 5/3x+1/3x=10+7/3x | | 23=4b-1+4b | | 4x-1/3=7/3 | | y=4+0.5 | | (1/2x)-3=(1/5x)+6 | | 5(x-2)+10=40 | | 80=105-5m |